Identification of Effective Restorers and Maintainers for Development of Rice Hybrids in Temperate Ecology - Sajad Hussain Dar, A.G. Rather, G.S. Sanghera M.A. Ahanger, M.A. Bhat, Noorul-Saleem, Manzor Ahmad, Syeed Talib, S.N. Kurashi and Nazir Ahmad (Electronic Journal of Plant Breeding, 2014)
Three cytoplasmic male sterile (CMS) lines with Wild Abortive (WA) CMS source were crossed with 9 rice genotypes to assess their restorer/maintainer behavior during 2011-12. Out of 27 test crosses evaluated, 10 restorers, 8 partial restorers and 9 partial maintainer cross combinations were categorized on the basis of pollen fertility and spikelet sterility. Three genotypes K-08-61, K-08-60 and Pusa Sughand-5 were found as effective restorers for all the three CMS lines with spikelet fertility above 83% in F1s for data pooled over environments, besides one more genotype K-08-59 depicted restoration only with the introduced CMS line IR-68888A.